KUALITAS LAPORAN KEUANGAN: PENGENDALIAN INTERNAL, TRANSPARANSI DAN KOMPETENSI SUMBER DAYA MANUSIA PADA BAZNAS PROVINSI JAMBI - Ester Salsanabila Jipa; Wiralestari Wiralestari; Rahayu Rahayu (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the influence of internal control, transparency, and human resource competence on the quality of financial reports at the National Amil Zakat Agency of Jambi Province. A quantitative approach was employed, with data collection conducted through the distribution of questionnaires to amil (zakat collectors) and Zakat Collection Units (UPZ). “Data analysis was performed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The research findings indicate that internal control and human resource competence significantly affect the quality of financial reports, while transparency shows no influence. Collectively, the three independent variables explain 79.5% of the variation in financial report quality (R² = 0.795), reflecting a high explanatory power of the model. The study concludes that the quality of financial reports is more dependent on internal organizational elements, particularly effective internal control and competent human resource capabilities. Therefore, efforts to improve financial report quality should prioritize strengthening control mechanisms and developing human resource capacities